Caracterização dos genes que codificam selenoproteínas em peixe-zebra (Danio rerio) - Macedo, Gabriel Teixeira de (2020)
Selenoproteins are selenocysteine (Sec)-containing proteins that exhibit numerous physiological functions, including redox homeostasis maintenance, thyroid hormones metabolism, selenium transport and chaperone-like activities. Compared to other organisms, zebrafish presents the highest number of selenoprotein-coding genes identified to date, and almost all selenoproteins found in human are present in the fish. Despite this, the variety of selenoproteins in zebrafish is little explored. In order to identify potential targets for translational studies, herein we analyzed the transcriptional status of selenoprotein genes in different tissues and life stages of zebrafish. Using RNA-seq data set from Sequence Reads Archive (SRA) experiments published at the DNA Data Bank of Japan (DDBJ), we determined the transcriptional levels of the 37 selenoproteins-coding sequences in brain, heart, gills, liver and skeletal muscle, comparing them throughout aging. Zebrafish selenoprotein-coding genes were confirmed by the presence of 3'-UTR SECIS structure in selenoprotein-coding mRNAs. Out of 37 selenoprotein genes analyzed here, we were unable to found a proper SECIS sequence for Selenoprotein J gene (selenoj). Overall, our transcriptome queries suggest all selenoprotein genes are actively transcribed in the tissues, with the exception of Selenoprotein E gene (selenoe). Finally, RNA-seq search revealed brain has the highest selenoprotein diversity and the transcription of 20 genes varied accordingly to age, with a peak at 16-month-old zebrafish brain. Collectively, the data from the present study support zebrafish and specially zebrafish adult brain as potent model organism for studies towards selenium and selenoproteins, focusing particularly on dio2, gpx1a, gpx4a, gpx4b, msrb1b, selenof, selenop, selenot1a, selenot2 selenow1, and selenow2a genes as targets for future translational studies.